Is there a level of competition intensity that maximizes investment in the mobile telecommunications industry? - Georges Vivien Houngbonon; Francois Jeanjean (International Telecommunications Society (ITS), 2014)
This paper empirically assesses the impact of the intensity of competition on investment in new technologies within the mobile telecommunications industry. Using firm level panel data and an instrumental variable estimation it finds an inverted-U relationship between competition intensity and investment. The intermediate level of competition intensity that maximizes investment stands at 62 percent, whereby competition intensity is measured by 1-Lerner index at the firm level. This means that the maximal level of investment is reached, on average, when the operating pro t represents 38 percent of total revenue. This result is rationalized through a theoretical model that yields an inverted-U relationship between competition and investment. It shows that the potential technological progress, measured by the impact of investment on the reduction of marginal cost, is the main determinant of the investment maximizing intermediate level of competition. The higher the potential technological progress, the lower the level of competition intensity that maximizes investment
Keywords: D21; D22; L13; L40; 330; Competition; Investment; Mobile Telecommunications